Insurance law handbook - John, Noleen; Hodgson, Laura; Weston-Simons, Charles (London [England] : Bloomsbury Professional, 2021)
"Insurance Law Handbook is a general, practical and accessible guide to all aspects of insurance law, including marine, aviation, employers' liability and professional indemnity. The updated 5th edition includes: - New chapter on cyber insurance - New chapter on public liability insurance - New chapter on comprehensive crime insurance - Coverage of the Insurance Act 2015 - Consideration of the implications of Brexit This specialist work combines a full range of information in one convenient, time-saving source of reference."--
Part 1 - The Insurance Contract -- Chapter 1: Contract of insurance -- Chapter 2: Terms in insurance contracts -- Chapter 3: Duration of insurance contracts -- Chapter 4: Insurable interest -- Chapter 5: Premiums -- Chapter 6: Policyholder duties -- Chapter 7: Policyholder protection -- Chapter 8: Global insurance programmes -- Part 2 - The Parties -- Chapter 9: Brokers -- Chapter 10: Underwriting agencies -- Chapter 11: Lloyd's -- Chapter 12: Insurance companies -- Part 3 - The Claim -- Chapter 13: Causation -- Chapter 14: Claims -- Chapter 15: Valuation of loss -- Chapter 16: Subrogation and assignment -- Chapter 17: Co-insurance -- Chapter 18: Double insurance and contribution -- Chapter 19: Average -- Chapter 20: Third Parties (Rights Against Insurers) Act 1930 -- Part 4 - Dispute Resolution -- Chapter 21: Arbitration -- Chapter 22: Court proceedings -- Chapter 23: Alternative dispute resolution -- Part 5 - Specific Types of Insurance -- Chapter 24: All risks insurance -- Chapter 25: Aviation insurance -- Chapter 26: Buildings and property insurance -- Chapter 27: Comprehensive crime insurance -- Chapter 28: Construction risks insurance -- Chapter 29: Cyber insurance -- Chapter 30: Directors' and officers' liability -- Chapter 31: Employers' liability insurance -- Chapter 32: Environmental insurance -- Chapter 33: Goods in transit insurance -- Chapter 34: Legal expenses insurance -- Chapter 35: Marine insurance -- Chapter 36: Motor vehicle insurance -- Chapter 37: Product liability insurance -- Chapter 38: Professional indemnity insurance -- Chapter 39: Public liability insurance -- Chapter 40: Reinsurance -- Chapter 41: War risks -- Part 6 - Regulatory Matters -- Chapter 42: Regulation of sales of insurance products -- Chapter 43: Insurance Business Transfers under the Financial Services and Markets -- Act 2000
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Insurance law -- England; Insurance law -- Wales; Insurance law; Law,Insurance law; Electronic books